Using Electrolyte Free Water Balance to Rationalize and Treat Dysnatremias - Shah, Sanjeev R.; Bhave, Gautam (Frontiers in Medicine, 2018)
Dysnatremias or abnormalities in plasma [Na+] are often termed disorders of water balance, an unclear physiologic concept often confused with changes in total fluid balance. However, most clinicians clearly recognize that hypertonic or hypotonic gains or losses alter plasma [Na+], while isotonic changes do not modify plasma [Na+]. This concept can be conceptualized as the electrolyte free water balance (EFWB), which defines the non-isotonic components of inputs and outputs to determine their effect on plasma [Na+]. EFWB is mathematically proportional to the rate of change in plasma [Na+] (dPNa/dt) and therefore is actively regulated to zero so that plasma [Na+] remains stable at its homeostatic set point. Dysnatremias are therefore disorders of EFWB and the relationship between EFWB and dPNa/dt provides a rationale for therapeutic strategies incorporating mass and volume balance. Herein, we leverage dPNa/dt as a desired rate of correction of plasma [Na+] to define a stepwise approach for the treatment of dysnatremias.